EFL Children’s Perception on Reading - Putu Santi Oktarina; Ni Kadek Tia Wiat Wilantari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Reading has a very significant effect towards individuals’ life. English inIndonesia as a foreign language, so there are many possibilities which the Englishlanguage students get difficulties in understading reading text. EFL young learners arealso still struggling to overcome their reading problems. This research was conducted tofind out the EFL children’s reading problem. The data were collected throughquestionnare and explained descriptively. The questionnare consists of ten questionswhich is made based on the rubric of reading. The respondents of this research were the20 students from the fourth grade. The results of the research that the EFL children’sreading problem are students seldom pay attention to punctuation in reading English,students always have difficulty to distinguish the pronunciation of words in English,students always need a long time to understand the reading text in English, studentsnever look for the main idea of the reading text which they read, students have poorreading habit because they unusual read in English or seldom read in English, studentsseldom even never understand the grammar structures in English when reading, studentsnever even seldom pay attention to the form or the content of the reading text which theyread, students never apply any strategies in reading English, students lack of vocabularywhen reading English so that they need a dictionary to comprehend the reading text inEnglish, and students do not like or not interested reading English because they areseldom reading in English. Thus, the questionnare show the EFL children’ readingproblem.